Victims of Sexual Violence on Campus in the News: Between Discrimination and Impartiality - Rosilawati, Yeni; Fadilla, Qholiva Yuni (Jurnal ILMU KOMUNIKASI, 2023)
The sexual assault committed by a Sriwijaya University (Unsri) lecturer on a student resulted in coercion. The lecturer then admitted his guilt to the student. The victim published her experience on the Twitter account @unsrifess until it received mainstream media attention. This research deconstructs the framing of Kompas.com and Detik.com about sexual violence in Unsri. Detik.com presents the victim as someone who has truly faced tragedy and injustice. On the other hand, Kompas.com often depicts the victim as a 'problematic' figure and as if the media is 'punishing' him through their reporting.